Sterilization incentives and associated regret among ever married women in India, NFHS, 2015-16 - Anjali Bansal; Laxmi Kant Dwivedi; P. Shirisha (BMC, 2022)
Abstract Objective Sterilization is the only family planning method that involves relatively large amount compensation. So, the study attempts to examine the role of incentives received against the sterilization procedures on the reporting of sterilization regret in India. Methods The study used data from the fourth round of National Family Health Survey, 2015-16, which gathered the information on sterilization regret from 1,94,207 ever-married women. Multivariate logistic analysis and predicted probabilities approach was used to study the effect of compensation received on the sterilization regret in India. Results Results show that women who have received compensation were 33% less likely to report sterilization regret. It was found that 70% of women who undergone sterilization in public facility didn't incur any expenditure, rather received incentives. It is observed that women who had undergone operation in private facility spent a large amount than women who had done their operation in public facility. The regret in the private facility mainly results from high out of pocket expenditure on sterilization procedures. Around eight percent of women regretted getting sterilized in a private hospital and received some compensation amount, vis a vis the six percent who regretted undergoing sterilization in public facility and received compensation. Conclusion The study calls for a need to standardize the cost of sterilization procedure in India's health facilities. A good alternative for reducing the cost could be Public-Private Partnership.